2022
DOI: 10.3390/v14122653
|View full text |Cite
|
Sign up to set email alerts
|

High APOBEC3B mRNA Expression Is Associated with Human Papillomavirus Type 18 Infection in Cervical Cancer

Abstract: The APOBEC3 (A3) proteins are cytidine deaminases that exhibit the ability to insert mutations in DNA and/or RNA sequences. APOBEC3B (A3B) has been evidenced as a DNA mutagen with consistent high expression in several cancer types. Data concerning the A3B influence on HPV infection and cervical cancer are limited and controversial. We investigated the role of A3B expression levels in cervical cancer in affected women positive for infection by different HPV types. Tumor biopsies from cancerous uterine cervix we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…50 The relationship between APOBEC3 activity and HPV infections has been extensively studied and has been shown to be intricate and type-specific. 21,36 On the one hand, HPV viral gene expression has been shown to promote APOBEC3 activity through many potential interactions, 51 including triggering DNA damage response pathways to enhance the viral replication and consequently upregulating APOBEC3. 36,51 On the other hand, APOBEC3 functions as a viral restriction factor reducing fitness of HPV, something that is also reflected in the genomes of alpha-HPVs which are strongly depleted of potential APOBEC3-targeted motifs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 The relationship between APOBEC3 activity and HPV infections has been extensively studied and has been shown to be intricate and type-specific. 21,36 On the one hand, HPV viral gene expression has been shown to promote APOBEC3 activity through many potential interactions, 51 including triggering DNA damage response pathways to enhance the viral replication and consequently upregulating APOBEC3. 36,51 On the other hand, APOBEC3 functions as a viral restriction factor reducing fitness of HPV, something that is also reflected in the genomes of alpha-HPVs which are strongly depleted of potential APOBEC3-targeted motifs.…”
Section: Discussionmentioning
confidence: 99%
“…21,36 On the one hand, HPV viral gene expression has been shown to promote APOBEC3 activity through many potential interactions, 51 including triggering DNA damage response pathways to enhance the viral replication and consequently upregulating APOBEC3. 36,51 On the other hand, APOBEC3 functions as a viral restriction factor reducing fitness of HPV, something that is also reflected in the genomes of alpha-HPVs which are strongly depleted of potential APOBEC3-targeted motifs. 36 Our model showed that the number of C to T mutations in a TCA and TCT context, which could correlate with APOBEC3 activity, increased significantly in the normal category over time when compared to high-grade (Figure 2C and Table S6).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, while initially thought to restrict HIV infection, A3A and A3G proteins can increase the viral mutational load, thereby reducing infectivity ( 5 ). High levels of A3B have been linked to human papillomavirus type 18 infection in cervical cancer (CESC) ( 6 ), as well as T-cell infiltration and improved outcomes in high-grade ovarian carcinoma (OV) ( 7 ). However, the precise functions and molecular mechanisms of A3s in cancer remain largely unclear, warranting further research.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, overexpression and abnormal activation of APOBEC3B contribute to the progression of various cancers, including drug resistance [9] , [10] , [11] . In cervical cancer, high expression of APOBEC3B is associated with infection of HPV-18 and proliferation and hypomethylation of cyclin D1 in cervical cancer cells [ 12 , 13 ]. In hepatocellular carcinoma (HCC), upregulation of APOBEC3B promotes cancer progression by interacting with polycomb repressive complex 2 (PRC2) to modulate the tumour microenvironment [14] .…”
Section: Introductionmentioning
confidence: 99%